P121 Characterising and managing issues with food-related quality of life in inflammatory bowel disease: a qualitative study of patients and healthcare professionals. (16th January 2018) - Czuber-Dochan, W; Morgan, M; Lomer, M; Lindsay, J O; Robert, G; Whelan, K
Abstract: Background: Inflammatory bowel disease (IBD) has a profound impact on diet and nutrition that creates limitations in psychosocial functioning and impacts quality of life (termed food-related quality of life, FR-QoL). The issues experienced and the management methods used by patients with IBD and healthcare professionals (HCPs) regarding FR-QoL are not well understood. Methods: Individual semi-structured interviews with 15 IBD patients reporting issues with FR-QoL; and two focus group interviews with 11 HCPs were audio recorded and transcribed verbatim. Pragmatic thematic analysis was used to analyse data, with NVivo 11 used for data management. Results: Fifteen patients with IBD (10 CD/5 UC) were purposively selected from UK hospital outpatient clinics (7 females, mean age 34.4 years; range 21–51 years). Individual interviews ranged from 39–70 min. Eleven HCPs (3 consultant gastroenterologists, three IBD registrars, two specialist dietitians, two IBD specialist nurses and one psychologist) participated in two focus groups over 2 h each. Patients perceived IBD as having a direct impact on their diet, particularly their food choices and enjoyment of food. This limited their daily life such as going out, socialising with friends and family, or personal relationships. Several factors, including limited understanding of IBD impact on body function and food digestion, fear of triggering a flare through eating, anxiety about making the right food choices, were perceived to contribute to impaired FR-QoL. Patients attempted various methods to improve FR-QoL including trial and error, food avoidance or exclusion, reducing portion size or frequency of eating; but few approaches were perceived to have the desired improvement in FR-QoL. Limited or no dietary advice from HCPs left patients feeling that food-related issues do not receive the same level of attention as medical management. During the focus groups, HCPs identified the factors affecting patients' diet and FR-QoL that needed greater attention and they were: IBD-related (e.g. newly diagnosed, acute inflammation, functional symptoms, strictures and stoma) and non-IBD related (e.g. pregnancy, allergies, likes/dislikes). HCPs acknowledged FR-QoL advice as a low priority in a consultation. HCPs recognised insufficient time in clinical consultations to address more complex issues. Some felt inadequately prepared to offer diet-specific advice, or assumed that other members of the multidisciplinary team provide diet-related care and advice. Conclusions: Both, patients and HCPs emphasised the need for more individualised care in relation to food and IBD and required quality and timely sources of information. The development and testing of interventions designed to address FR-QoL is required.